Deshidratación de la guayaba, una opción para su aprovechamiento integral - Barbosa, Helber; Morales, Alicia Lucía; Osorio, Coralia; Jiménez, Aleyda (Universidad Nacional de Colombia, 2018)
Guayaba-Psidium guajava